Penerapan Dynamic Audio Pada 2D Endless Runner Game Menggunakan Pure Data - Ade Darmawan; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
2D platformer game is a genre game where players move characters through a side camera and are required to pass existing obstacles to achieve certain goals. Techniques in game development to add to the playing experience are also growing very rapidly. Can be taken an example of the application of dynamic audio. The use of dynamic audio in the game will provide the advantage of using static audio by entering multiple assets for each movement. This research uses Pure Data to implement dynamic audio in endless 2D game runners. Pure Data has a visual way to program sound, namely by connecting small boxes together with virtual cables. Therefore the use of Pure Data is to apply dynamic audio to endless 2D game runners that are highly preferred with consideration of convenience in applying them. The results of this study prove that from predetermined designs obtained valid results and successfully run on 2D runner endless games that have FPS are not significantly different from the use of static audio. The average FPS obtained is 62.4 FPS for dynamic audio and 62.1 FPS for static audio which can be ignored as well as the application of dynamic audio in 2D Endless Runner Games does not provide performance.